Acceptance towards Ar-Rahnu product among customers of Bank Rakyat Senawang / Fakrul Razi Abdulatif - Abdulatif, Fakrul Razi (Faculty of Business and Management, 2011)
The objective of this study is to examine the factors of acceptance towards Ar-Rahnu product among customers of Bank Rakyat Senawang. Islamic pawn-broking (Ar- Rahnu) has a big impact to the society development and hence contributes to economic growth. This study also aims to investigate what factors are able to attract customers who are in need for quick cash to choose Ar-Rahnu product instead of conventional pawn-broking or other financial products. Considering this objective, the current study tends to develop a model, a theoretical framework of doing the Shariah view and product attributes could attract customers from both Muslims and Non-Muslims community to accept and to choose the Ar-Rahnu product offered by Bank Rakyat Senawang specifically. Based on this study, the sampling design selected is non-probability sampling, which is the judgment sampling. The data will be collected by self-administered questionnaires distributed to 50 respondents chosen among the customers of Bank Rakyat Senawang who come to pledge their gold through the Ar-Rahnu product. The responses obtained will be analyzed by using SPSS